Nonlinear stability of eccentrically stiffened S-FGM elliptical cylindrical shells in thermal environment. (November 2016) - Duc, Nguyen Dinh; Tuan, Ngo Duc; Tran, Phuong; Cong, Pham Hong; Nguyen, Pham Dinh
Abstract: This paper has studied on the nonlinear buckling and postbuckling of a eccentrically stiffened functionally graded thin elliptical cylindrical shells surrounded on elastic foundations in thermal environment. Material properties are graded in the thickness direction according to a Sigmoid power law distribution ( s -FGM) in terms of the volume fractions of constituents with metal - ceramic - metal layers. The elliptical cylindrical shells have stiffeners in two directions (longitudinal and transversal) on the external surface and inside surface surrounded on elastic foundations. The typical point in the study is both elliptical cylindrical shells and stiffeners having temperature-dependent properties are deformed under temperature simultaneously, leading to the equation to determine buckling thermal loads with both sides that are dependent on temperature, so the iterative algorithms are proposed to numerical technique in this case. The equilibrium and compatibility equations for the moderately elliptical cylindrical shells are derived by using the classical shell theory (CST) taking into account both geometrical nonlinearity in von Karman sense and initial geometrical imperfection. By applying the Galerkin method and using a stress function, the effects of material and geometrical properties, temperature-dependent material properties, elastic foundations and stiffeners on the buckling and postbuckling loading capacity of eccentrically stiffened FGM elliptical cylindrical shells in thermal environments are studied simultaneously for first time. Highlights: The nonlinear stability. The functionally graded thin elliptical cylindrical shells reinforced by stiffeners. The shell surrounded on elastic foundations in thermal environment. Material properties are graded by a Sigmoid power law distribution ( s -FGM) with metal - ceramic - metal layers. Used CST, the Galerkin method and stress function.